(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Polymerase Chain Reaction (PCR) technique using specific primer can be used to detect transgenes. The present study was undertaken to detect salmon growth hormone (GH) gene in transgenic tilapia (Oreochromis niloticus) by PCR. DNA was extracted from F1 Tilapia generated by crossing transgenic parents. Two primers were designed to amplify a part of the region of GH gene sequence, which was used to make transgenic tilapia. To confirm the specificity of the selected primer, PCR was performed on diluted DNAs, extracted from tilapia fin tissues. GH transgene sequences (1500 bp) were successfully amplified from transgenic fish in this study. The specificity of the primers was found to be high in detecting the salmon GH transgenes. The PCR-based method therefore, could be used for fast and easy screening of transgenic fish for this gene. J. Environ. Sci. & Natural Resources, 8(2): 47-49 2015